A quasi-experimental intervention to assess the effectiveness of a physician-delivered tobacco cessation intervention in India: A detailed study protocol. (17th March 2017) - Panda, Rajmohan; Mahapatra, Sandeep; Gaurav, Kumar; Pati, Sanghamitra; Mathur, Manu Raj
Introduction: Tobacco cessation is the most important, cost-effective preventive maintenance that clinicians can offer study participants who use tobacco. There is lack of preparedness among primary care physicians in delivering cessation interventions. There are also limited studies which record the effectiveness of cessation interventions in the Indian context. This study is designed to evaluate the effectiveness of brief and intensive tobacco cessation interventions delivered by trained primary care providers in two states of India. Methods and Analysis: A quasi-experimental study design has been adopted for the study with around 20 primary care practices, selected from four districts of two states in India (Odisha and Rajasthan). Brief (3A) and Intensive tobacco (5A) cessation intervention services will be provided to two groups of tobacco users, respectively. Both groups will be followed up for 6 months to determine the effectiveness of the cessation interventions. The cost-effectiveness of the services will also be documented at the end of the study. The entire study will be completed in 24 months, of which the final 6 months will be reserved for study participant follow-up and quit rate evaluation. When comparing the two groups, differences between proportions will be assessed by chi-square test and differences between means with t -test. The conventional significance level of 0.05 will be used in all analyses in order to reject the null hypothesis of no difference between groups. We will use difference-in-differences methods to assess the impact of the interventions on physicians' behavior to deliver tobacco cessation in their clinical practice. Conclusion: The study is in participant recruitment phase.